Novel Verrucomicrobiota strains associated with plant root tissue enhance plant growth and suppress bacterial wilt in tomato - Choi, Minseo; Kaari, Manigundan; Lee, Hyoung Ju; Lee, Seon-Woo (Frontiers in Microbiology, 2025)
IntroductionRhizosphere microbes interact with plant roots, playing a crucial role in promoting plant growth and alleviating both biotic and abiotic stresses. Our previous study identified putative keystone taxa associated with bacterial wilt (BW) resistance in tomato plants. Among these taxa, bacteria in phylum Verrucomicrobiota remain poorly characterized due to challenges in laboratory cultivation. Here, we aimed to isolate novel Verrucomicrobiota strains from tomato rhizosphere soil using various carbon and streptomycin-enriched culture media combined with microbiota analysis.Methods16S rRNA amplicon sequencing was conducted to identify the suitable carbon source for isolating novel Verrucomicrobiota strains from tomato rhizosphere soil. The plant growth promotion and biocontrol assay were conducted to understand the potential of Verrucomicrobiota strains. Root hair developmental study was used to observe the tomato root hair formation by safranin-O staining assay.ResultsMicrobiota analysis revealed the carbon-source dependent microbial community structure in the enrichment cultures. Verrucomicrobiota strains were the most abundant in the cultures enriched with grounded plant roots and streptomycin. A total of 27 novel bacteria, including two Verrucomicrobiota strains (V1 and V2), were isolated from different enrichment cultures. In-planta plant growth promotion (PGP) assay, strain V2 demonstrated a higher plant fresh weight than strain V1. Disease severity assessment showed that V1 was more effective in controlling BW than V2.ConclusionThese findings suggest that plant-associated Verrucomicrobiota members are involved in plant-beneficial interaction in the rhizosphere. Our study presents a novel strategy for isolating previously uncultivated Verrucomicrobiota strains from the tomato rhizosphere using carbon and antibiotic-enriched cultures.